Return to Play Following a Shoulder Stabilization Surgery in Athletes With Anterior Shoulder Instability. A Systematic Review of Systematic Reviews - Nimse, Ashutosh (Auckland University of Technology, 2022)
Introduction: Traumatic shoulder dislocations are prevalent in contact or collision sports, and a majority of them occur anteriorly, causing anterior shoulder instability (ASI). Despite advanced arthroscopic repair techniques to treat ASI, it remains unclear when an athlete should RTP. The RTP criteria are inconsistent, and RTP timeframes show variability after a shoulder stabilization surgery. Aims & Objectives: The aim of this systematic review is to appraise all the systematic reviews that have explored RTP outcomes following a shoulder stabilization surgery in athletes having anterior shoulder instability. Methods: All systematic reviews that have explored RTP outcomes such as RTP timeframes, strength, and patient-reported outcome measures were critically appraised using a measurement tool to assess the systematic reviews (AMSTAR-2) tool. Results: The RTP time frame was the only outcome reported in all the studies in this review. A significant gap exists in the reported PROM and strength outcomes. The majority of studies showed a moderate quality of rigor in AMSTAR 2 scoring. Overall, the literature is insufficient and lacks high-quality systematic reviews exploring RTP outcomes following anterior shoulder stabilization surgery. Conclusion: Looking at moderate-quality evidence, there is a need for validation of multi-level RTP criteria.
Keywords: Anterior shoulder instability; Shoulder stabilization; Return to play; Outcome measures